ANALISIS KUALITAS KEHIDUPAN KERJA, KINERJA, DAN KEPUASAN KERJA PADA CV DUTA SENENAN JEPARA - Noor Arifin (Jurnal Economia, 2012)
Abstract: Analysis of Work Quality, Performance, and Job Satisfaction in CV. Duta Senenan Jepara. This study aims to analyze the effect of the quality work life of employees to their performance, analyze the effect of the quality of work life to the job satisfaction, and analyze the effect of the job satisfaction to employee performance. Variables used in this study are: quality of work Life developed by Wayne Cascio 1992; the performance of employees, developed by Elmuti and Kathawala, 1997; and variables Job Satisfaction, provided by Robbin, 1996 and Wexley et al, 1992. The sample of this study consists of 65 employees. The data Analysis were performed using structural equation modeling with partial least square approach. The result suggests that the quality of work life affects the performance; the satisfaction affects the employee performance; and the quality of working life has no effect on employee satisfaction.